GLOBAL STABILIZATION OF LINEAR SYSTEMS WITH BOUNDED-CONTROLS USING STATE-DEPENDENT SATURATION FUNCTIONS - Zhou, Bin; Duan, Guangren; Kong, He (Journal of systems science and complexity, 2011)
By using the so-called SP-stable polynomials, this paper reconsiders the problem of global stabilization of linear systems with input saturation. Firstly, a new nonlinear feedback law consisting of parallel connections of saturation functions by means of the so-called state-dependent saturation function is proposed for global stabilization of chains of integrators system. The state-dependent saturation function allows increasing the control energy when some of the states are badly scaled and can improve significantly the transient performances of the closed-loop system. Secondly, this type of global stabilization nonlinear feedback laws is extended to a class of linear systems that can be globally stabilized by bounded controls. Numerical examples show the effectiveness of the proposed approach.